Nietzsche : the man and his philosophy - Hollingdale, R. J. (Cambridge : Cambridge University Press, 1999)
This classic biography of Nietzsche, first published in the 1960s, was enthusiastically reviewed at the time. The biography is now reissued with its text updated in the light of recent research. Hollingdale's biography remains the single best account of the life and works for the student or non-specialist. The biography chronicles Nietzsche's intellectual evolution and discusses his friendship and breach with Wagner, his attitude towards Schopenhauer, and his indebtedness to Darwin and the Greeks. It follows the years of his maturity and his mental collapse in 1889. The final part of the book considers the development of the Nietzsche legend during his years of madness. R. J. Hollingdale, one of the preeminent translators of Nietzsche, allows Nietzsche to speak for himself in a translation that transmits the vividness and virtuosity of Nietzsche's many styles. This is the ideal book for anyone interested in Nietzsche's life and work to learn why he is such a significant figure for the development of modern thought.
Title from publisher's bibliographic system (viewed on 17 Sep 2019).
Keywords: Nietzsche, Friedrich Wilhelm, -- 1844-1900.